ANALYSIS OF ECONOMIC ADAPTATION PATTERNS OF COASTAL COMMUNITIES IN THE ERA OF CLIMATE CHANGE: A SYSTEMATIC REVIEW OF SUSTAINABLELIVELIHOOD STRATEGIES - Dwi Apriyanti Kumalasari; Bahrun Thalib; Silvia Ekasari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research analyses the economic adaptation patterns of coastal communities in the era of climate change through a systematic review of sustainable livelihood strategies. Given that coastal communities are highly vulnerable to the impacts of climate change, this study highlights the importance of diversifying income sources and adopting innovative environmentally friendly practices as an effort to enhance economic resilience. This research uses the literature method. The results show that successful adaptation involves active community participation, government policy support, and access to technology and education. Close cooperation between stakeholders, including government, non-governmental organisations and local communities, is required to support the implementation of effective adaptation strategies. The research concludes that capacity building, enhancing local knowledge, and facilitating access to resources and technology play a vital role in ensuring the success of sustainable economic adaptation patterns for coastal communities. With an integrative and participatory approach, coastal communities can increase their resilience to climate change and achieve long-term prosperity.